Rule extraction for support vector machine using input space expansion - Pitiranggon, Prasan; Benjathepanun, Nunthika; Banditvilai, Somsri; Boonjing, Veera (My University, 2011)
Fuzzy Rule-Based System (FRB) in the form of human comprehensible IF-THEN rules can be extracted from Support Vector Machine (SVM) which is regarded as a black-boxed system. We first prove that SVM decision network and the zero-ordered Sugeno FRB type of the Adaptive Network Fuzzy Inference System (ANFIS) are equivalent indicating that SVM's decision can actually be represented by fuzzy IFTHEN rules. We then propose a rule extraction method based on kernel function firing strength and unbounded support vector space expansion. An advantage of our method is the guarantee that the number of final fuzzy IF-THEN rules is equal or less than the number of support vectors in SVM, and it may reveal human comprehensible patterns. We compare our method against SVM using popular benchmark data sets, and the results are comparable. © 2011 Springer-Verlag Berlin Heidelberg.
Keywords: Fuzzy IF-THEN rules; Pattern classification; Rule extraction; Support Vector Machine